Computational protocol to perform a spatiotemporal reconstruction of an epidemic - Riccardo Nodari; Matteo Perini; Luca Fois; Lodovico Sterzi; Ester Luconi; Folco Vaglienti; Claudio Bandi; Elia Biganzoli; Massimo Galli; Francesco Comandatore (STAR Protocols, 2023)
Summary: Here, we present a computational protocol to perform a spatiotemporal reconstruction of an epidemic. We describe steps for using epidemiological data to depict how the epidemic changes over time and for employing clustering analysis to group geographical units that exhibit similar temporal epidemic progression. We then detail procedures for analyzing the temporal and spatial dynamics of the epidemic within each cluster. This protocol has been developed to be used on historical data but could also be applied to modern epidemiological data.For complete details on the use and execution of this protocol, please refer to Galli et al. (2023).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.